N, P, and K Fertilization for Newly Established Tall Fescue - D. W. Sweeney; J. L. Moyer; J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2016)
Second-year production of tall fescue was affected by nitrogen (N) and phosphorus (P) fertilization rates at Site 1 in 2014 and only by N fertilization rates at Site 2 in 2015, with little effect from potassium (K) fertilization at either site.
Keywords: pastures; hay